A Cross Sectional Study of Knowledge and attitudes levels about Polio Vaccination among selected sample of Technical Institute \ AL-Suwaira staff members - Muhsin, Jasim Mohammed; Jawad, Ahmed Kadhim (Diyala Journal of Medicine, 2019)
Background: The previous laboratory investigations confirmed local polio case was informed on 28th January 2000 and another two wild polio cases were reported from Resafa \ Baghdad province in 2014. The date of onset of these cases were February and April 2014 and both cases were connected to 2013 of Syria outbreak. Objective:To evaluate the knowledge and attitudes levels towards polio vaccination among staff of Technical Institute - AL-Suwaira. Patients and Methods: A study of cross-sectional design consisted of 170 a selected samples of Technical Institute \ AL-Suwaira staff members. Collected during January 2018.The knowledge and attitudes levels estimated by using typical design of self-administered questionnaire. Descriptive statistics were used to explain the results. Results: Over all, 170 participants reacted to the questionnaire by a response rate of 93.5%. All respondents established a good knowledge and positive attitudes levels to poliovirus vaccination. Mean knowledge score (built on11 knowledge questions) and mean attitude score (built on 10 attitudes statements) of participants about polio vaccine were 14.45±2.38 and 26.5±4.5 respectively. The mainstream of respondents agreed that all children should be taken the polio vaccine (88.2%), and the sterility concerns that associated with polio vaccines (14.1%). Television (n=126, 39%) and Internet (n = 66, 21%) were the main social media sources that used by staff members to educate and modify themselves about polio vaccination. Knowledge defects were recognized in the management issues and how to dealing with vaccines (45.9%), the incubation period of poliovirus infection (38.8%) and the consequences of the poliovirus infection (56.5%) on the victims. Conclusion: Staff members of Technical Institute \ AL-Suwaira showed a good knowledge and positive attitudes levels about polio vaccination. Even though the statistics are indicative of knowledge gaps of participants, further studies are needed to assess these levels for better education program against polio.